Cardiology career satisfaction: a little academic activity goes a long way - deFilippi, Christopher R. (Frontiers in Cardiovascular Medicine, 2024)
The professional landscape for clinical cardiologists along with most physicians has changed dramatically in the last decade in the United States. By the end of 2020, 87% of cardiologists were integrated with a health system (employed or part of a professional services agreement) (1). The Inova health system, located in northern Virginia outside of Washington DC, is consistent with this trend. Physicians transitioning to a large employer can feel dissatisfaction from a lack of autonomy, pressure from “one-size-fits-all” productivity targets, and outcomes judged by patient satisfaction scores. Productivity demands at their worst can lead to the phenomenon of “burnout” with a paradox that higher demands with greater clinical productivity can lead to a lower sense of personal accomplishment. There can be serious consequences of “burnout”. A recent meta-analysis showed that a sense of lower personal accomplishment results in 47% more patient safety incidents adversely impacting all within a health system (2). How then might this be addressed in a constructive manner to promote professional well-being, expertise and autonomy with recognition that health systems often work with razor thin financial margins? Thinking as a clinician one considers both a peer-reviewed evidence base and anecdotal experience to address this issue.